Editors' introduction. (21st October 2019) - Homan, Shane; Strong, Catherine
Abstract : Welcome to this issue of Popular Music History that is emblematic of major changes at the journal through deeply sad circumstances due to the passing of long-time editor Dave Laing. This issue provides considerable focus upon histories of progressive rock, a genre that is undertaking something of a renaissance in scholarship in the past few years.